Rebel without Causes: The 1960s Thai Pop Music and Bangkok Youth Culture - Viriya Sawangchot (Communicare : Journal of Communication Studies, 2016)
In this paper, I would like to acknowledge that 1960s to the 1970s American popular culture, particularly in rock‘n’ roll music, have been contested by Thai context. In term of this, the paper intends to consider American rock ‘n’ roll has come to function as a mode of humanization and emancipation of Bangkok youngster rather than ideological domination. In order to understand this process, this paper aims to focus on the origins and evolution of rock ‘n’ roll and youth culture in Bangkok in the 1960s to 1970s. The birth of pleng shadow will be discussed in this context as well.